Penguatan Moral di Kalangan Remaja di Desa Tarai Bangun Kampar - Imron Rosidi; Khotimah Khotimah (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
This article discusses about the empowerment of moral enforcement among Muslim youth in Desa Tarab Mulia Tarai Bangun Kampar. This empowerment employs preaching and question-answer methods. It focuses on the empowerment which is located in al-Muhajirin Mosque. This empowerment succeeds in giving moral understandings and empowerment among Muslim youth in Desa Tarab Mulia. It demonstrates on how Muslim youth is being attached to the mosque as the center of moral empowerment in Indonesia.